Does Private Schooling Increase Adult Earnings? Cohort-Level Evidence for U.S. States - Reilee L. Berger; John V. Winters (Institute for the Study of Labor (IZA), 2016)
Public schooling in the U.S. has numerous critics, many of whom suggest that alternatives such as providing vouchers for private schools may be more effective. This paper combines decennial census and American Community Survey data for various years to examine the relationship between cohort-level private schooling rates and later earnings during adulthood. We also explore differences by sex and examine the role played by the quantity of education completed and occupational attainment. We find a significant positive relationship between private schooling rates and adult earnings for women but a small relationship for men.
Keywords: I20; J24; R50; 330; private schooling; school choice; K-12 education; earnings; wages